(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
In this article, the architectural monuments of our country, in particular, the historical monuments built during the Timurid era, have been studied by foreign researchers and the information presented in their works is discussed in detail.